1973
DOI: 10.1002/oms.1210070807
|View full text |Cite
|
Sign up to set email alerts
|

Collisional activation spectra. Behavior of [C3H7O]+ and other [CnH2n+1O]+ ions

Abstract: Collisional activation spectra have identified (CH,),C=OH (a), C,H,CH=OH (d), CH,=OC,H, (h) and CH,CH=OCH3 (i) as stable ion structures. Evidence is presented for a variety of pathways for their formation, including anchimeric assistance and hydrogen migration in less stable isomers. The fragmentation behavior of a number of [C,H,,,,O]+ isomers of n = 2 to 5 shows that extensive rearrangements are common, but that some reactions appear to be useful for ion structure elucidation. One reaction identified is unu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0

Year Published

1976
1976
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(19 citation statements)
references
References 16 publications
2
17
0
Order By: Relevance
“…Several authors have investigated the detailed fragmentation of [CH 2 = O + CH 2 CH 3 ] ions ( m/z 59) into the ions at m/z 41 and 31, corresponding to the losses of H 2 O and C 2 H 4 ,20,, 25–30 respectively, with a considerable extent of hydrogen scrambling prior to decomposition 7,. 8 Thus the decomposition of the m/z 59 ion is not described in this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have investigated the detailed fragmentation of [CH 2 = O + CH 2 CH 3 ] ions ( m/z 59) into the ions at m/z 41 and 31, corresponding to the losses of H 2 O and C 2 H 4 ,20,, 25–30 respectively, with a considerable extent of hydrogen scrambling prior to decomposition 7,. 8 Thus the decomposition of the m/z 59 ion is not described in this study.…”
Section: Resultsmentioning
confidence: 99%
“…The mass spectra of gem‐dicthoxyalkanes (RR′C(OCH 2 CH 3 ) 2 ) have been investigated by several authors 2–6. The decomposition of the m/z 59 ion ([M − OCH 2 CH 3 ] + : CH 2 = O + CH 2 CH 3 ) from diethoxymethane (CH 2 (OCH 2 CH 3 ) 2 , MW 104 ( 1 )) into the m/z 41 and 31 ions has been reported;7,, 8 however, the detailed fragmentation mechanisms of 1 +· , especially the fragmentation of the m/z 47 ion (protonated formic acid, CH(OH) = O + H), have not yet been discussed.…”
mentioning
confidence: 99%
“…McLafferty and Sakai (10) have reported the collision-induced dissociation (CID) mass spectra of a few C 5 H l 1 0 t ions, while Zahorszky (1 1) has surveyed briefly the unimolecular ion chemistry of higher members of the series. The most extensive study has been that of Audier et al (12) of the C5HIIOt ions of nominal structures 1 to 7 (Scheme I ) prepared by electron impact methods.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, the chemistry of isomers 3 and 4, which cannot be prepared directly by EI, has been studied much less. McLafferty and Sakai [5] reported that ions of nominal structures 3 and 4, prepared by protonation (C~chemical ionization) of propylene oxide and oxetan, respectively, gave highenergy CID mass spectra similar to the CIO mass spectrum of 2, prepared by EI, implying isomerization of all three to a common structure or mixture of structures. A detailed CID study by Harrison et al [12] showed that 2 and 3 gave very similar OD spectra, suggesting isomerization to a common structure or mixture of structures.…”
mentioning
confidence: 97%
“…Among the species that have been studied in detail are the [C 3H70]+ isomers 1 and 2 (Scheme I) [2][3][4][5][6][7][8][9][10][11][12], produced mainly by electron impact. It has been clearly established, from both unimolecular fragmentation studies [7][8][9] and collision-induced dissociation (CIO) studies [5,12], that 1 and 2 are stable, noninterconverting species in the gas phase. By contrast, the chemistry of isomers 3 and 4, which cannot be prepared directly by EI, has been studied much less.…”
mentioning
confidence: 99%